1996
DOI: 10.1093/schbul/22.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine Eligibility Among State Hospital Patients

Abstract: Connecticut State Hospital's entire resident population (n = 1,300) was screened on an arbitrary target day to determine eligibility for clozapine. Sixty percent of 803 patients with schizophrenia or schizoaffective disorder diagnoses met Food and Drug Administration (FDA)- approved criteria for clozapine use as judged by review of past medication trial records and by the responsible physicians. Eighty-eight percent of these patients were medically cleared, and of those cleared, 63 percent agreed to clozapine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
1
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 17 publications
1
75
1
5
Order By: Relevance
“…Subsequent studies have confirmed these results (Rosenheck et al, 1997;Buchanan et al, 1998;Pickar et al, 1992;Breier et al, 1994;Essock et al, 1996;Conley et al, 1999). The advantage of clozapine over a firstgeneration antipsychotic medication was also found in partially responsive, community-based, schizophrenic patients (Kane et al, 2001;Buchanan et al, 1998;Breier et al, 1994).…”
Section: Discussionmentioning
confidence: 84%
“…Subsequent studies have confirmed these results (Rosenheck et al, 1997;Buchanan et al, 1998;Pickar et al, 1992;Breier et al, 1994;Essock et al, 1996;Conley et al, 1999). The advantage of clozapine over a firstgeneration antipsychotic medication was also found in partially responsive, community-based, schizophrenic patients (Kane et al, 2001;Buchanan et al, 1998;Breier et al, 1994).…”
Section: Discussionmentioning
confidence: 84%
“…Não ficou claro se as vantagens das medicações psicóticas atípicas na prevenção da recaída eram decorrentes de sua melhor eficácia, sua melhor tolerabilidade ou à melhor aderência ao tratamento. Para os dados reunidos de estudos individuais, apenas a risperidona (Csernansky et al, 2002;Marder et al, 2003) e a olanzapina , mas não a clozapina (Essock et al, 1996a(Essock et al, e 1996bRosenheck et al, 1999aRosenheck et al, , 1999bRosenheck et al, e 2000Tamminga et al, 1994) ou a amisulprida (Speller et al, 1997), mostraram ser significativamente superiores aos APGs (Leucht et al, 2003b). Embora o índice de recaída não fosse significativamente menor, o tratamento com a clozapina se mostrou associado à permanência mais longa na comunidade (Leucht et al, 2003b) e a menores taxas de readmissão hospitalar (Essock et al, 1996a(Essock et al, e 1996b.…”
Section: Eficácia Dos Antipsicóticos De Primeira Geraçãounclassified
“…A clozapina revelou superioridade na melhora dos sintomas positivos durante ECR de longo prazo (mais de 6 meses), em que foi comparada ao haloperidol (Kane et al, 2001), efeito que seria confirmado futuramente em estudos abertos (Essock et al, 1996a(Essock et al, e 1996bRosenheck et al, 1999aRosenheck et al, e 1999b. A clozapina demonstrou habilidade para melhorar significativamente os sintomas negativos quando comparada aos APGs num estudo aberto com duração de 1 ano (Meltzer et al, 1989).…”
Section: Eficácia Dos Antipsicóticos De Segunda Geraçãounclassified
“…A bout one-third of all people with schizophrenia are substantially resistant to drug treatment; this has been a consistent finding over time (1,2). Because of this resistance, there was much enthusiasm after the clinical introduction of clozapine.…”
mentioning
confidence: 92%